THE RENEWAL AND UPGRADE OF LEGAL REGULATION OF TELECOMMUNICATIONS IN THE EU - M. B. Kasenova (Московский журнал международного права, 2019)
INTRODUCTION. The choice of the strategic vector of the socio-economic development of modern states is focused on the “digital economy”, and telecommunications offer critical economic importance and commercial value. Approaches to the legal regulation of the telecommunications sector, which the European Union demonstrates, are now acquiring an important practical significance for many states. This article considers the simultaneous adoption by the European Parliament and the Council on December 11, 2018 of two acts of “secondary EU law” (Directive (EU) 2018/1972 on the establishment of the European Electronic Communications Code and Regulation (EU) 2018/1971 establishing the Body of European Regulators for electronic communications and the Agency for support thereof) to be the key factor that marks the “newest” stage in telecommunications regulation, which enhances the appeal to their analysis.MATERIALS AND METHODS. The presented article is based on doctrinal studies of Russian and foreign scientists in the field of European law, electronic communications, as well as on regulatory documents and the roots of the European Union's legal system. Formal-logical, historical-legal, technical-legal, comparative-legal and SWOT-analysis methods as well as other general scientific and special legal methods were the methodological basis for the preparation of this article.RESEARCH RESULTS. The dynamic development of the regulation of relations in the field of telecommunications in the European Union indicates a consistent, systematic and complex formation, development and improvement of the relevant regulations, and institutional frameworks in their organic correlation. The proposed periodization of telecommunication regulations highlights the main stages in which relevant EU legal instruments were developed and improved, defining the crux of two related processes: establishing a common regulatory framework, enshrined in EU legal documents, and improving the institutional organization of regulations at EU level.DISCUSSION AND CONCLUSIONS. The author of the presented article believes that the adoption of the EU Electronic Communications Code is a highlevel codification act, offering legal certainty and harmonizing the regulation of the telecommunications sector. Modernizing the function of the Body of European Regulators through electronic communications (BEREC) and the Agency for Support of BEREC, just as with the institutional structures of special competencies, leads to the further development of the institutional framework of the European Union in the telecommunications sector.